Supervisi Di Sdn Mangkubumen Lor No. 15 Surakarta Tahun Ajaran 2016/2017 - Saraswati, Erma yunitta, Muhroji, M.Si., M.Pd., S.E (2017)
This study aims to describe how planning supervision at SDN Mangkubumen Lor No. 15 Surakarta, describes heimplementation of supervision at SDN Mangkubumen Lor No.15 Surakarta, describes how evaluation, and follow-up supervision at SDN Mangkubumen Lor No. 15 Surakarta Academic Year 2016/2017. This type of descriptive qualitative research and case study design. Data collection techniques used interviews, observation, and documentation. The validity of this research data using techniques Miles and Huberman. The results showed that: 1) The supervision planning program includes designing the schedule of supervision plementation, class observation and planning data that need to be prepared for supervision activities. 2) Implementation of supervision at SDN Mangkubumen Lor No. 15 Surakarta consists of the implementation of academic supervision through class visits and non-academic supervision by checking administrative completeness such as class administration data covering syllabus, prota, promos, RPP, and others. 3) The supervision evaluation program at SDN Mangkubumen Lor No. 15 Surakarta observes 4 aspects of Master's competence, ranging from paedagogic aspect, social aspect, professional aspect, and personality aspect. Evaluation of supervision using evaluation of academic supervision covering principal evaluate learning process in class which is adjusted to RPP made by teacher, while evaluation of non-academic supervision of headmaster evaluate completeness of school administration data. The follow-up form of the supervision evaluation provides input input on teacher shortcomings in written and oral form and provides workshops, seminars, training and KKG.